Sub-versions : trans-national readings of modern Irish literature - Ross, Ciaran (DQR studies in literature, 2010)
From Swift¿́¿s repulsive shit-flinging Yahoos to Beckett¿́¿s dying but never quite dead moribunds, Irish literature has long been perceived as being synonymous with subversion and all forms of subversiveness. But what constitutes a subversive text or a subversive writer in twenty-first-century Ireland? The essays in this volume set out to redefine and rethink the subversive potential of modern Irish literature. Crossing three central genres, one common denominator running through these essays whether dealing with canonical writers like Yeats, Beckett and Flann O¿́¿Brien, or lesser known contemporary writers like Sebastian Barry or Robert McLiam Wilson, is the continual questioning of Irish identity ¿́¿ Irishness ¿́¿ going from its colonial paradigm and stereotype of the subaltern in MacGill, to its uneasy implications for gender representation in the contemporary novel and the contemporary drama. A subsidiary theme inextricably linked to the identity problematic is that of exile and its radical heritage for all Irish writing irrespective of its different genres. Sub-Versions offers a cross-cultural and trans-national response to the expanding interest in Irish and postcolonial studies by bringing together specialists from different national cultures and scholarly contexts ¿́¿ Ireland, Britain, France and Central Europe. The order of the essays is by genre. This study is aimed both at the general literary reader and anyone particularly interested in Irish Studies.